2008
DOI: 10.1016/s1472-6483(10)60306-9
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancies and live births following ICSI with testicular spermatozoa after repeated implantation failure using ejaculated spermatozoa

Abstract: The use of testicular spermatozoa for IVF/intracytoplasmic sperm injection (ICSI) is currently indicated exclusively for patients with azoospermia, since a favourable outcome is expected even when very few spermatozoa are present in the ejaculate. Here, a series of four couples with long-standing male factor infertility and multiple failed IVF/ICSI cycles are described. In all couples, the use of ejaculated spermatozoa for ICSI resulted in poor embryo quality and repeated implantation failure. Testicular sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 29 publications
0
41
1
1
Order By: Relevance
“…Lastly, Weissman et al showed that testicular spermatozoa was useful to overcome long-standing recurrent implantation failure in a group of four couples who failed to conceive by ICSI using ejaculated sperm (31). A plausible reason for the improved ICSI outcomes in the aforementioned series might be the lower SDF levels in testicular specimens compared with ejaculated counterparts (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Weissman et al showed that testicular spermatozoa was useful to overcome long-standing recurrent implantation failure in a group of four couples who failed to conceive by ICSI using ejaculated sperm (31). A plausible reason for the improved ICSI outcomes in the aforementioned series might be the lower SDF levels in testicular specimens compared with ejaculated counterparts (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Neither study compared IVF-ICSI outcomes between ejaculated and matched testicular derived sperm from the same individual. Additionally, these studies did not stratify for the cohort of men who have had repeated IVF-ICSI failure, a group that may benefit from testis-derived sperm [10, 11, 40, 41]. Our small case series documents a possible benefit for this population.…”
Section: Discussionmentioning
confidence: 93%
“…TİB'li hasta grubunda testiküler spermatozoa kullanımı ile daha yüksek gebelik oranları elde edilmesine rağmen bu konu ile ilgili daha fazla randomize kontrollü çalışmaya ihtiyaç vardır. 49,52 Karyotip Tayini TİB'li hastalarda kromozomal anomali insidansı %2,5 olup normal populasyona göre daha yüksek olduğundan bu hasta grubunda çiftlere karyotip analizi önerilmektedir. bir veya iki blastomer biyopsisi ve blastokist aşa-masında yapılan hücre biyopsisidir.…”
Section: Sperm Dna Fragmantasyonuunclassified